17β -estradiol Hormone and Interleukin 1-beta Change Related to Menopause in the Women with Rheumatoid Arthritis (Asian Journal of Pharmaceutics (AJP), 2019)
The depletion of 17β-estradiol-2 (17β-E2) is one of the factors that cause the risk of rheumatoid arthritis (RA)in females in the case of menopause. The aim of this study is to investigate whether the change in 17β-E2 levelsand interleukin 1-beta (IL-1β) is associated with menopause in RA women and whether there is a relationshipbetween them. 96 RA women were divided into three groups as follows: Group 1 (women of reproductiveage) – 30, Group 2 (premenopausal women) – 32 (menstrual or normal menstrual period without menstruationfor a period of not >6 months, and Group 3 (postmenopausal women) – 34 women in menopause (menopausefor at least 12 months). Serum levels of 17β-E2, IL-1β, and anti-cyclic citrullinated peptide were evaluated byenzyme-linked immunosorbent assay. The results showed that a change in concentration of 17β-E2 resultedin excessive production of IL-1β in women during reproductive age, premenopausal, and postmenopausalcompared to female control. Furthermore, there is a highly inverse correlation between IL-1β and 17β-E2 inthe serum of pre- and post-menopausal RA women. On the other hand, the study showed a positive correlationbetween IL-1β and sex hormones 17β-E2 in women of reproductive age who suffer from RA. Moreover, thestudy confirmed that the most risk factor is 17β-E2. The study showed that a lack of 17β-2 concentration aftermenopause causes an increased concentration of IL-1β and this, in turn, stimulates the development of RAdisease during menopause. Menopause-associated 17β-E2 deficiency plays the major role in the pathogenesisof RA.